High-fluidity and high-strength alcohol type transparent coating glue and preparation method thereof
By developing high-flow, high-strength alcohol-type transparent coating glue, using specific components and process steps, the limitations of existing sealing materials in yellowing resistance, odor, corrosion and complex production processes are solved, and high tensile strength, leveling performance and storage stability are achieved. It is suitable for a variety of substrates and meets environmental protection requirements.
Patent Information
- Application Number
- CN202411871778.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-11
AI Technical Summary
Existing polymer sealing materials have shown limitations in moisture resistance, insulation, mildew resistance, dust resistance, etc., such as poor yellowing resistance, large odor, corrosiveness to certain substrates, and complex production process.
A high-flow high-strength alcohol-type transparent coating glue was developed, and a high tensile strength, leveling performance and storage stability were prepared by using alkoxy-terminated silane, gas-phase or precipitation white carbon black, silane coupling agent and other components, and through specific process steps such as vacuum dehydration, planetary dynamic mixing, etc.
This alcohol-type transparent coating has high tensile strength, leveling performance and storage stability. It can effectively resist water, moisture and dust, and is corrosion-free to most substrates. It has a simple and easy-to-operate process and meets environmental protection requirements.
Smart Images

Figure CN119592295A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer sealing materials, and in particular to a high-fluidity and high-strength alcohol-type transparent coating adhesive and a manufacturing method thereof. Background Art
[0002] With the rapid development of global electronic information technology, the scale of the electronic and electrical appliance market is also expanding. During the use of circuit boards and electronic components, various environmental factors such as salt spray, mold, dust, etc. often lead to corrosion, aging, mildew, short circuit and other problems; in order to protect the circuit boards, people usually apply a layer of coating glue on the electronic component circuit boards to achieve moisture-proof, insulation, mildew-proof, dust-proof and other effects.
[0003] The mainstream silicone flowing coating adhesives on the market are currently divided into three categories: ketone oxime type, deethanol type and demethanol type. The deketone oxime transparent flowing coating adhesive, such as the Chinese patent document CN106190015B, discloses a solvent-free silicone coating adhesive and a preparation method thereof. The silicone coating adhesive includes the following raw materials in parts by mass: 70-100 parts of hydroxyl-terminated polydimethylsiloxane, 10-30 parts of film enhancer, 2-6 parts of cross-linking agent, 0.1-0.8 parts of catalyst, and 0.5-1.5 parts of tackifier to form a silicone coating adhesive with good high and low temperature resistance, insulation, bonding, moisture resistance, shock resistance and corona resistance, but it itself has great limitations such as: poor yellowing resistance, strong odor, and corrosiveness to copper and PC sheets.
[0004] Some deethanolized flowing coating adhesives have good bonding and sealing properties for metals, plastics and other materials, are corrosion-free, resistant to aging, and resistant to high and low temperatures, but still have poor yellowing resistance and irritating odor. Compared with the first two, the advantages of deethanolized transparent flowing adhesives are yellowing resistance, low odor, and no corrosion to most substrates, but there are also problems such as low strength, poor fluidity, and poor storage. The best solution is to modify the surface of the reinforcement material without sacrificing its fluidity and meeting the properties of high strength and good storage.
[0005] Chinese patent document CN112011092A discloses a method for modifying white carbon black, which comprises the following steps: pre-hydrolysis of a silane coupling agent, slurry preparation, acidic low-temperature adsorption, alkaline high-temperature grafting, and drying. The method for modifying white carbon black greatly improves production efficiency and white carbon black modification effect while improving the utilization rate and grafting rate of the silane coupling agent; however, the method is complicated to operate, time-consuming, and not conducive to production.
[0006] Therefore, developing a glue with simple production process and high strength and high fluidity can better fill this market gap. Summary of the invention
[0007] The present invention is achieved through the following technical solutions:
[0008] A high-fluidity and high-strength alcohol-based transparent coating adhesive comprises the following components in parts by weight:
[0009] Base material part:
[0010]
[0011] Auxiliary agent part:
[0012]
[0013]
[0014] Preferably, the alkoxy-terminated silane has a structural formula as shown in formula (I), and a viscosity of 500 Pa.s to 80000 Pa.s at 25°C;
[0015]
[0016] Wherein n≥1, R is one of methyl, methoxy and ethoxy.
[0017] Preferably, the reinforcing filler has a specific surface area of 130 to 480 m 2 / g of fumed hydrophilic silica, with a specific surface area of 130 to 380 m 2 / g of fumed hydrophobic silica, with a specific surface area of 150 to 380 m 2 / g of precipitated hydrophilic white carbon black, with a specific surface area of 150-380m 2 / g of at least one of precipitated hydrophobic silica.
[0018] Preferably, the filler surface modifier is a silane coupling agent, specifically: one or two of mercaptopropyl triethoxysilane, octamethylcyclotetrasilazane, divinyldisilane, dimethyldichlorosilazane, hexamethyldisilazane, divinyldisilane, γ-aminopropyltriethoxysilane (KH-550), γ-(2.3-epoxypropyloxy)propyltrimethoxysilane (KH-560).
[0019] Preferably, the modifier solvent is anhydrous ethanol and deionized water.
[0020] Preferably, the plasticizer is at least one of dimethyl-terminated polydimethylsiloxane, single-end alkoxy polydimethylsiloxane, MDT silicone oil, and a paraffin mixture.
[0021] Preferably, the crosslinking agent is one or more of methyltrimethoxysilane, methylphenyldimethoxysilane, methylphenyltriethoxysilane, methyl orthosilicate, propyl orthosilicate, methyltriethylsilane, methylpropyldimethoxysilane, methylpropyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, methylvinyldimethoxysilane, polymethyltrimethoxysilane, polymethyltriethoxysilane, polypropyltrimethoxysilane, 1,2-bis(trimethoxysilyl)ethane, and 1,2-bis(triethoxysilyl)ethane.
[0022] Preferably, the coupling agent is vinyl tris (2-methoxyethoxy) silane, bisamino hydrolyzed oligomer, γ-aminopropyl trimethoxy silane, γ-aminopropyl triethoxy silane, N- (β-aminoethyl) -γ-aminopropyl trimethoxy silane, N- (β-aminoethyl) -γ-aminopropyl triethoxy silane, bis- [3- (trimethoxysilyl) -propyl] -ethylenediamine, bis- [3- (triethoxysilyl) -propyl] -ethylenediamine, N- [3- (trimethoxysilyl) -propyl] -n-butylamine, N,N-dimethyl-3-aminopropyl trimethoxy silane, N-n- At least one of butyl-3-aminopropyltriethoxysilane, 3-(diethylenetriamino)propyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 2-cyanoethyltriethoxysilane, ureidopropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, isocyanatepropyltrimethoxysilane, and isocyanatepropyltriethoxysilane.
[0023] Preferably, the catalyst is a titanium complex, a zirconate complex, a chelated tin, lithium octoate, or an organic aluminum compound.
[0024] The present invention also provides a method for manufacturing the high-fluidity and high-strength alcohol-based transparent coating adhesive, comprising the following steps:
[0025] a. Add 100 parts by weight of alkyl-terminated silane and 5-30 parts of reinforcing filler at 120-150°C and a vacuum degree of 0.08-0.099 MPa, dehydrate and blend for 60-180 minutes, add 2-10 parts of filler surface modifier and 1-5 parts of modifier solvent into a planetary power mixer after cooling, blend at 60°C for 60-180 minutes, then heat to 120-150°C to remove low molecular weight substances for 30-180 minutes, and cool to obtain a base material;
[0026] b. At room temperature, add the above base material into a planetary mixer or a high-speed disperser, and then add 1 to 4 parts of a cross-linking agent, 0.2 to 1 part of a coupling agent, and 0.03 to 0.5 parts of a catalyst into the planetary mixer or a high-speed disperser together with the base material, and carry out a chemical reaction for 30 to 180 minutes at a vacuum degree of 0.06 to 0.099 MPa and a rotation speed of 10 to 800 rpm to prepare a high-fluidity and high-strength alcohol-based transparent coating adhesive.
[0027] The present invention has but is not limited to the following beneficial effects:
[0028] 1. It has high tensile strength and can protect circuit boards and electronic components from wear and pollution;
[0029] 2. It has high leveling performance and is easy to construct.
[0030] 3. It can be made into an environmentally friendly product; the product can meet the requirements of RoHS directive and REACH regulations, and can maintain high fluidity without adding plasticizers, so it can also pass FDA food grade certification.
[0031] 4. Good transparency, components coated on PCB are clearly visible.
[0032] 5. It has excellent waterproof, moisture-proof and dust-proof properties; it has excellent properties of anti-salt spray, anti-aging, shockproof, anti-leakage, anti-corrosion, anti-mildew and anti-parts loosening; it has good insulation properties.
[0033] 6. It has excellent durability, heat resistance and water boiling resistance, and its performance changes little from low temperature -40℃ to high temperature 200℃. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to clearly demonstrate the specific implementation methods of the present invention and certain detection technologies used in the experiments, the implementation methods and the technologies used will be described below, mainly in the form of drawings.
[0035] Figure 1 This is the production process diagram of high-fluidity and high-strength alcohol-based transparent coating adhesive. DETAILED DESCRIPTION
[0037] The specific implementation methods of the present invention are explained with the aid of examples. Except that the technology used for detection does not impose any form of limitation on the present invention, some schemes in the described embodiments belong to part of the embodiments of the invention. The embodiments obtained by ordinary technical operators in this field without creative results all belong to the protection scope of the present invention.
[0038] Embodiment 1:
[0039] A high-fluidity and high-strength alcohol-based transparent coating adhesive, comprising the following components in parts by weight, and a preparation method thereof;
[0040] Base rubber: 100 parts of alkoxy-terminated silane (kinematic viscosity at 25°C is 1500 Pa.s), fumed silica (specific surface area is 150m 2 / g) 15 parts, temperature 120 ° C, vacuum degree 0.09 MPa, dehydrate and blend for 120 minutes under nitrogen protection, add 4 parts of octamethylcyclotetrasilazane after cooling, and 2 parts of deionized water are added into a planetary power mixer, blend for 80 minutes at 60 ° C, then heat to 150 ° C, vacuum degree 0.09 MPa, dehydrate for 120 minutes, and cool to obtain the base rubber.
[0041] Additive part: add the above base material to a planetary mixer, then add 3 parts of methyltrimethoxysilane and 1 part of vinyltrimethoxysilane, mix and stir evenly for 20 minutes at a vacuum degree of 0.09 MPa and a rotation speed of 300 rpm, then add 0.2 parts of diamino hydrolyzed oligomer, 0.2 parts of γ-aminopropyltriethoxysilane, and 4 parts of titanium complex (Jianyi Chemical Ti9000), and carry out chemical reaction under nitrogen protection conditions at a vacuum degree of 0.09 MPa and a rotation speed of 300 rpm for 90 minutes. The product performance indicators are shown in Table 1.
[0042] Embodiment 2:
[0043] A high-fluidity and high-strength alcohol-based transparent coating adhesive, comprising the following components in parts by weight, and a preparation method thereof;
[0044] Base rubber: 100 parts of alkoxy-terminated silane (kinematic viscosity at 25°C is 5000 Pa.s), fumed silica (specific surface area is 150 m 2 / g) 20 parts, temperature 120 ° C, vacuum degree 0.09 MPa, dehydrate and blend for 120 minutes under nitrogen protection, add 2 parts of hexamethyldisilazane, 2 parts of divinyldisilane and 3 parts of deionized water into a planetary power mixer after cooling, blend at 60 ° C for 60 minutes, then raise the temperature to 150 ° C, vacuum degree 0.09 MPa, dehydrate for 120 minutes, and cool to obtain the base rubber.
[0045] Additive part: add the above base material to a planetary mixer, then add 4 parts of methyl orthosilicate and 2 parts of methylpropyldiethoxysilane, mix and stir evenly for 20 minutes at a vacuum degree of 0.09 MPa and a rotation speed of 300 rpm, then add 0.2 parts of γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, 0.2 parts of -[3-(triethoxysilyl)-propyl]-ethylenediamine, and 3 parts of zirconate complex, and carry out chemical reaction at a vacuum degree of 0.09 MPa and a rotation speed of 300 rpm under nitrogen protection conditions for 90 minutes. The product performance indicators are shown in Table 1.
[0046] Embodiment 3:
[0047] A high-fluidity and high-strength alcohol-based transparent coating adhesive, comprising the following components in parts by weight, and a preparation method thereof;
[0048] Base rubber: 100 parts of alkoxy-terminated silane (kinematic viscosity at 25°C is 10,000 Pa.s), fumed silica (specific surface area is 150 m 2 / g) 20 parts, temperature 120 ° C, vacuum degree 0.09 MPa, dehydrate and blend for 120 minutes under nitrogen protection, 4 parts of mercaptopropyl triethoxysilane and 20 parts of ionized water are adjusted to pH 4 using glacial acetic acid, then the temperature is raised to 60 ° C and stirred for 45 minutes to completely hydrolyze the silane coupling agent, and then added into a planetary power mixer together with the cooled base glue, the temperature is raised to 60 ° C and blended for 80 minutes, and then the temperature is raised to 150 ° C, the vacuum degree is 0.09 MPa, and the base glue is obtained after dehydration for 120 minutes and cooling.
[0049] Additive part: add the above base material to a planetary mixer, then add 4 parts of methylphenyltrimethoxysilane and 0.5 parts of propyltriethoxysilane, mix and stir evenly for 20 minutes at a vacuum degree of 0.09 MPa and a rotation speed of 300 rpm, then add 0.2 parts of bis-[3-(trimethoxysilyl)-propyl]-ethylenediamine, 0.2 parts of γ-aminopropyltriethoxysilane, and 0.01 parts of chelated tin, and carry out chemical reaction at a vacuum degree of 0.09 MPa and a rotation speed of 300 rpm under nitrogen protection conditions for 90 minutes. The product performance indicators are shown in Table 1.
[0050] Embodiment 4:
[0051] A high-fluidity and high-strength alcohol-based transparent coating adhesive, comprising the following components in parts by weight, and a preparation method thereof;
[0052] Base rubber: 100 parts of alkoxy-terminated silane (kinematic viscosity at 25°C is 20,000 Pa.s), fumed silica (specific surface area is 150 m 2 / g) 20 parts, temperature 120 ° C, vacuum degree 0.09 MPa, dehydrate and blend for 120 minutes under nitrogen protection, add γ-aminopropyltriethoxysilane (KH-550) 6 parts, (a mixture of deionized water and anhydrous ethanol 1:9) 3 parts, use glacial acetic acid to adjust the pH value to 4-5, heat to 70 ° C and stir for 60 minutes. After the silane coupling agent is completely hydrolyzed, add it together with the cooled base material into a planetary power mixer, blend for 80 minutes at 60 ° C, then heat to 150 ° C, vacuum degree 0.09 MPa, dehydrate for 120 minutes, and cool to obtain the base rubber.
[0053] Additive part: add the above base material to a planetary mixer, then add 4 parts of polymethyltrimethoxysilane, mix and stir evenly for 20 minutes at a vacuum degree of 0.09 MPa and a rotation speed of 300 rpm, then add 0.2 parts of N-dimethyl-3-aminopropyltrimethoxysilane, 0.2 parts of 3-(diethylenetriamine)propyltrimethoxysilane, and 0.02 parts of chelated tin, and carry out chemical reaction under nitrogen protection conditions at a vacuum degree of 0.09 MPa and a rotation speed of 300 rpm for 90 minutes. The product performance indicators are shown in Table 1.
[0054] Embodiment 5:
[0055] A high-fluidity and high-strength alcohol-based transparent coating adhesive, comprising the following components in parts by weight, and a preparation method thereof;
[0056] Base rubber: 100 parts of alkoxy-terminated silane (kinematic viscosity at 25°C is 30,000 Pa.s), fumed silica (specific surface area is 150 m 2 / g) 15 parts, temperature 120 ° C, vacuum degree 0.09 MPa, dehydrate and blend for 120 minutes under nitrogen protection, add γ-(2.3-glycidoxy)propyltrimethoxysilane (KH-560) 6 parts, (a mixture of deionized water and anhydrous ethanol 1:9) 3 parts, use glacial acetic acid to adjust the pH value to 4-5, heat to 70 ° C and stir for 60 minutes, after the silane coupling agent is completely hydrolyzed, add it into a planetary power mixer together with the cooled base material, blend at 60 ° C for 80 minutes, then heat to 150 ° C, vacuum degree 0.09 MPa, dehydrate for 120 minutes, and cool to obtain the base rubber.
[0057] Additive part: add the above base material to a planetary mixer, then add 4 parts of polymethyltrimethoxysilane and 1 part of vinyltrimethoxysilane, mix and stir evenly for 20 minutes at a vacuum degree of 0.09 MPa and a rotation speed of 300 rpm, then add 0.2 parts of -(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 0.2 parts of 3-aminopropyltrimethoxysilane and 0.02 parts of chelated tin, and carry out chemical reaction at a vacuum degree of 0.09 MPa and a rotation speed of 300 rpm under nitrogen protection conditions for 90 minutes. The product performance indicators are shown in Table 1.
[0058] Comparative Example 1:
[0059] The method for preparing a high-flowability and high-strength transparent coating adhesive in this comparative example is basically the same as that in Example 4, except that the catalyst is replaced with 3 parts of diisopropyl diacetoacetate.
[0060] Comparative Example 2: The method for preparing a high-flowability and high-strength transparent coating adhesive in this comparative example is basically the same as that in Example 4, except that the fumed silica is not treated with any silazane and only 10 parts of white carbon black are added.
[0061] Example 6
[0062] Preparation process and performance testing of high-fluidity and high-strength alcohol-based transparent coating adhesive;
[0063] The present invention provides a simple production process (the process is as follows Figure 1 As shown) and has high flowability, high strength alcohol-type transparent coating adhesive and its manufacturing method. It is characterized by using base adhesive, reinforcing filler, filler surface modifier, modifier solvent to modify the surface of white carbon black in a simple and easy-to-operate manner, and then adding plasticizer, crosslinking agent, coupling agent, and catalyst to react. The product has high tensile strength while maintaining good flowability, is non-corrosive to most substrates and has excellent bonding properties. GB / T 24267-2009 "Flame Retardant Sealant for Construction" adopts the test methods in GB / T 22083-2008 "Classification and Requirements of Building Sealant"; GB13477 "Measurement Method of Building Sealant"; for testing, and the results are shown in Table 1.
[0064] Table 1 Coating adhesive performance test results
[0065]
[0066] It can be seen from Table 1 that the silicone rubber developed in the present invention has the characteristics of high fluidity, fast surface drying time, high strength, etc.; it has a transparent and flowing appearance, a surface drying speed between 6 and 15 minutes, a fluidity between 6.5 and 12.6 cm / min, a tensile strength between 1.61 and 3.61, and good storage stability without yellowing.
[0067] From Examples 1 to 5, it can be seen that as the viscosity of the alkoxy-terminated silane increases, the overall fluidity of the rubber decreases and the surface drying time shortens, which is not conducive to construction. However, using an alkoxy-terminated silane with too low a viscosity will also lead to poor strength. Therefore, the best solution is to use an alkoxy-terminated silane with a kinematic viscosity of 20,000 Pa.s at (5°C).
[0068] From the comparison between Examples 2 and 3 and Examples 1 and 2 and Comparative Example 1, it can be seen that a very small amount of chelated tin (≤0.02%) can be used to achieve a good catalytic effect, and the rubber sample itself does not turn yellow and is resistant to aging. In Example 2, the tack-free time is prolonged after aging using a zirconate complex as a catalyst. It is speculated that the free alcohol in the silicone rubber reacts with the polysiloxane in a balanced manner under the catalysis of the organic metal zirconium to generate (CH 3 O)(CH 3 ) 2 SiO 2 Group.
[0069] From Example 4 comparing Examples 1 and 2, it can be seen that the addition of phenyl-containing silane can greatly improve the hardness and tensile strength of the glue sample after curing. This may be because phenyl-containing silane can increase the crosslinking density of the glue sample, promote and increase the degree of polymerization of silane, so that the glue sample has a faster surface drying speed and higher hardness and strength as a whole.
[0070] From Comparative Examples 1 and 2, it can be seen that diisopropyl diacetoethyl titanate is not suitable for this type of glue sample as a catalyst. After the aging test, the glue sample turns yellow as a whole, affecting the overall appearance of the glue sample; in Comparative Example 2, the leveling property is poor, and the whole is solidified after the aging test. It is speculated that the reason is that the hydroxyl content of the gas-phase silica that has not been surface-modified with silazane is too high, resulting in the formation of cross-links with a spatial network structure inside the glue sample.
Claims
1. A high-fluidity, high-strength alcohol-based transparent coating adhesive, characterized in that The composition comprises the following components by weight: Base material part: Auxiliary agent part:
2. The high-fluidity and high-strength alcohol-based transparent coating adhesive as claimed in claim 1, characterized in that; The alkoxy-terminated silane has a structural formula as shown in formula (I), and has a viscosity of 500 Pa.s to 80,000 Pa.s at 25°C; Wherein n≥1, R is one of methyl, methoxy and ethoxy.
3. The high-fluidity and high-strength alcohol-based transparent coating adhesive as claimed in claim 1, characterized in that; The reinforcing filler has a specific surface area of 130 to 480 m 2 / g of fumed hydrophilic silica, with a specific surface area of 130 to 380 m 2 / g of fumed hydrophobic silica, with a specific surface area of 150 to 380 m 2 / g of precipitated hydrophilic white carbon black, with a specific surface area of 150-380m 2 / g of at least one of precipitated hydrophobic silica.
4. The high-fluidity and high-strength alcohol-based transparent coating adhesive as claimed in claim 1, characterized in that; The filler surface modifier is a silane coupling agent, specifically: one or two of mercaptopropyl triethoxysilane, octamethylcyclotetrasilazane, divinyldisilane, dimethyldichlorosilazane, hexamethyldisilazane, divinyldisilane, γ-aminopropyltriethoxysilane (KH-550), and γ-(2.3-epoxypropyloxy)propyltrimethoxysilane (KH-560).
5. The high-fluidity and high-strength alcohol-based transparent coating adhesive as claimed in claim 1, characterized in that; The modifier solvent is anhydrous ethanol and deionized water.
6. The high-fluidity and high-strength alcohol-based transparent coating adhesive as claimed in claim 1, characterized in that; The plasticizer is at least one of dimethyl-terminated polydimethylsiloxane, single-end alkoxy polydimethylsiloxane, MDT silicone oil, and a chain alkane mixture.
7. The high-fluidity and high-strength alcohol-based transparent coating adhesive as claimed in claim 1, characterized in that; The crosslinking agent is one or more of methyltrimethoxysilane, methylphenyldimethoxysilane, methylphenyltriethoxysilane, methyl orthosilicate, propyl orthosilicate, methyltriethylsilane, methylpropyldimethoxysilane, methylpropyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, methylvinyldimethoxysilane, polymethyltrimethoxysilane, polymethyltriethoxysilane, polypropyltrimethoxysilane, 1,2-bis(trimethoxysilyl)ethane, and 1,2-bis(triethoxysilyl)ethane.
8. The high-fluidity and high-strength alcohol-based transparent coating adhesive as claimed in claim 1, characterized in that; The coupling agent is vinyl tris (2-methoxyethoxy) silane, bisamino hydrolyzed oligomer, γ-aminopropyl trimethoxy silane, γ-aminopropyl triethoxy silane, N-(β-aminoethyl)-γ-aminopropyl trimethoxy silane, N-(β-aminoethyl)-γ-aminopropyl triethoxy silane, bis-[3-(trimethoxysilyl)-propyl]-ethylenediamine, bis-[3-(triethoxysilyl)-propyl]-ethylenediamine, N-[3-(trimethoxysilyl)-propyl]-n-butylamine, N,N-dimethyl-3-aminopropyl trimethoxy silane, N-n-butyl -At least one of 3-aminopropyltriethoxysilane, 3-(diethylenetriamino)propyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltrimethoxysilane, γ-(2,3-epoxypropyloxy)propyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 2-cyanoethyltriethoxysilane, ureidopropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, isocyanatepropyltrimethoxysilane, and isocyanatepropyltriethoxysilane.
9. The high-fluidity and high-strength alcohol-based transparent coating adhesive as claimed in claim 1, characterized in that; The catalyst is a titanium complex, a zirconate complex, a chelated tin, lithium octoate, or an organic aluminum compound.
10. A method for manufacturing a high-fluidity, high-strength alcohol-based transparent coating adhesive as claimed in any one of claims 1 to 9, characterized in that The steps include: a. Add 100 parts by weight of alkyl-terminated silane and 5-30 parts of reinforcing filler at 120-150°C and a vacuum degree of 0.08-0.099 MPa, dehydrate and blend for 60-180 minutes, add 2-10 parts of filler surface modifier and 1-5 parts of modifier solvent into a planetary power mixer after cooling, blend at 60°C for 60-180 minutes, then heat to 120-150°C to remove low molecular weight substances for 30-180 minutes, and cool to obtain a base material; b. At room temperature, add the above base material into a planetary mixer or a high-speed disperser, and then add 1 to 4 parts of a cross-linking agent, 0.2 to 1 part of a coupling agent, and 0.03 to 0.5 parts of a catalyst into the planetary mixer or a high-speed disperser together with the base material, and carry out a chemical reaction for 30 to 180 minutes at a vacuum degree of 0.06 to 0.099 MPa and a rotation speed of 10 to 800 rpm to prepare a high-fluidity and high-strength alcohol-based transparent coating adhesive.
Citation Information
Patent Citations
A solvent-free silicone coating adhesive and its preparation method
CN106190015B
Modification method for white carbon black
CN112011092A